Vocações Tangenciais - uma casa-atelier de escultura em madeira - José Augusto Sanches Albergaria Giro (2020)
This study proposes to understand the particular conditions of an artistic residence consisting of a dwelling articulated with a workshop space dedicated to wooden carving - a studio-house. This dissertation aims to expose tangential points of interest between the fields of sculpture and architecture, confronting my academic career with the frequency of the discipline of Escultura en Madera, at the Pontifical Catholic University of Chile Escuela de Arte to enhance the conception of an architectural device adapted to the work of a contemporary sculptor. The significance of a project that combines tools from the domain of sculpture with the craft of architecture is deepened to reflect on the experience and logics of producing a workshop space for wood carving, in order to reconvert a spa into atelier articulated with the house.